Honduras : Education Resilience Case Report - World Bank (Washington, DC, 2014)
This country report and the data presented herein are a product of the piloting of the RES-360 tool in Honduras. First, national level data was collected from government strategic plans, focus groups with Ministry of Education leadership, and secondary sources such as national studies on youth violence. Next, focus groups were conducted with teachers, parents, and students from two selected schools in low income neighborhoods affected by violence in the capital, Tegucigalpa.